Internal Migration and Mortality: The Case of Finland - Fjalar Finnäs; Jan Saarela (SAGE Publishing, 2008)
In light of possibilities and limitations of data from the Finnish population register, and the general demographic development of Finland, this paper illuminates the complex interrelation between internal migration and mortality. We explore the roles played by health selection, birth region, and migration as a potentially harmful event. A five per cent random sample from a longitudinal data ﬁ le that contains deaths for a period of 24 years is used. The focus is on people aged 40-59 years living in Southern Finland, who are defined by birth region and time since immigration. We find some indications of a healthy-migrant effect, but also that migrants may have integration difficulties or that they are negatively selected with regard to health behaviours and lifestyles. In line with previous studies on Finland, birth region is found to be a very decisive mortality determinant.